The centipedes (Arthropoda, Myriapoda, Chilopoda) from Colombia: Part I. Scutigeromorpha and Scolopendromorpha - Chagas-Jr, Amazonas; Chaparro, Elisa; Jiménez, Sebastián Galvis; Triana, Hernán Darío Triana; D., Eduardo Flórez; Seoane, José Carlos Sícoli (Zootaxa, 2014)
This study presents an updated list of centipedes of the orders Scutigeromorpha and Scolopendromorpha from Colombia based on data from the literature, the World Catalogue of Centipedes (CHILOBASE), and specimens examined in museum collections. Four families, nine genera, 37 species and four subspecies are listed. One species belongs to Scutigeromorpha, and 36 species and four subspecies to Scolopendromorpha. Eleven species and four subspecies of scolopendromorphs are recorded for the first time from Colombia. Newportia Gervais, 1847 is the most diverse genus with 12 species and three subspecies. Six species of Scolopendromorpha are endemic. Three species—Otostigmus inermis Porat, 1876, O. scabricauda (Humbert & Saussure, 1870) and Cryptops iheringi Brölemann, 1902—are deleted from the fauna of Colombia. The Andean Región in Colombia has the most records of Scutigeromorpha and Scolopendromorpha. Maps showing the geographical distribution are given for the orders, genera, and some species.